Psalm 100 : 3 a short note - Villiers, T. de (Old Testament Essays, 2002)
This short note wishes to pose a twofold reality in the process of Bible Translation (BT), namely that there is both a process of exegesis and interpretation involved. This writer presupposes that what manifests itself to the reader as a translation of Holy Scripture is certainly the result of one or both of the above processes. Psalm 100 : 3 is used as an illustration of this reality. The use of text-critical information in three English translations is critically considered. This article concludes with a few remarks on responsible use of such information also in presenting the translation to the reader as Holy Scripture.
free